2019
DOI: 10.1210/clinem/dgz026
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone Exposure Reduced the Risk of All-Cause Mortality in Insulin-Treated Patients with Type 2 Diabetes Mellitus

Abstract: Context The long-term safety and benefit of pioglitazone use in combination with insulin are still uncertain. Objective This study compared the risks of all-cause mortality and major cardiovascular (CV) events between pioglitazone users and nonusers receiving insulin therapy. Design, Setting and Patients We conducted a 13-year retrospective cohort study by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Data from these studies provide strong evidence to support the use of pioglitazone for secondary stroke prevention, and it is possible that the results could be extended in the future to populations without a history of stroke [13]. Based on real-world data, the effect of pioglitazone on stroke varies according to the different clinical characteristics of patients and the interaction with other glucose-lowering agents [14][15][16][17][18]. A meta-analysis of randomized-controlled trials (RCTs) revealed that pioglitazone reduced the risk of stroke in patients with a history of established cardiovascular (CV) diseases [19].…”
Section: Introductionmentioning
confidence: 97%
“…Data from these studies provide strong evidence to support the use of pioglitazone for secondary stroke prevention, and it is possible that the results could be extended in the future to populations without a history of stroke [13]. Based on real-world data, the effect of pioglitazone on stroke varies according to the different clinical characteristics of patients and the interaction with other glucose-lowering agents [14][15][16][17][18]. A meta-analysis of randomized-controlled trials (RCTs) revealed that pioglitazone reduced the risk of stroke in patients with a history of established cardiovascular (CV) diseases [19].…”
Section: Introductionmentioning
confidence: 97%
“…M1 macrophage infiltration accompanies whitening of brown fat, suggestive of BAT dysfunction (Figure 2 ). Some phytochemicals and phthalates also can promote M2 macrophage polarization and beiging in WAT[ 111 , 112 ].…”
Section: Clinical and Mechanistic Evidencementioning
confidence: 99%
“…53 In addition, recent data showed that pioglitazone in combination with insulin may reduce the risks of all-cause mortality and non-cardiovascular death in people with T2D. 54 No additional considerations are required when combining…”
Section: Co-administration With Other Antidiabetic Medicationsmentioning
confidence: 99%
“…However, a recent systematic review suggested that pioglitazone is a feasible adjunct to insulin therapy 53 . In addition, recent data showed that pioglitazone in combination with insulin may reduce the risks of all‐cause mortality and non‐cardiovascular death in people with T2D 54 …”
Section: Co‐administration With Other Antidiabetic Medicationsmentioning
confidence: 99%